Determinants of Entrepreneurial Attitudes in Relation to Students of Economics and Non-Economics - Monika Jakubiak; Krystyna Buchta (Studia i Materiały)
The issue of entrepreneurship has become extremely popular in recent years. The reason behind the phenomenon ought to be seen in the growing significance of entrepreneurship in the development of modern economies, emphasis on competence development and individuals’ activity. The literature of the subject discusses academic entrepreneurship with growing frequency. The issue is associated with the changing role of the modern university. At present, universities are becoming the place where students’ attitudes and competences are shaped in the context of challenges posed by the increasingly competitive labor market and innovative economy. The subject matter of the present paper pertains to entrepreneurial competences and attitudes of students representing selected university courses. The objective of the paper is to identify entrepreneurial competences and factors determining pro-entrepreneurial attitudes of respondents. The authors attempt to evaluate students’ readiness to undertake vocational activities, especially these associated with self-employment. The study allowed a comparative analysis of respondents’ competences and attitudes with regard to entrepreneurial activities to be conducted. The following research questions were posed: Do the students of the assessed university courses in economy who are considered more inclined and predestined to establish a business feel more prepared to do so and declare higher entrepreneurial competences than remaining respondents? Does the particular course of studies determine the decision pertaining to becoming self-employed?